Hijrah Menuju Harapan Baru dan Kejayaan Islam - Peter Bruno Sarbini (Seri Filsafat Teologi, 2021)
Hijrah is a very important event for Muslims, a milestone in the formation of Islamic civilization in Yathrib or Medina. Many lessons can be learned from this hijrah. The hijrah of the Prophet Muhammad and his companions was not a running away from reality, but a decision based on divine revelation to build new strength and hope that one day they could return with honor, dignity, glory and transformation. The opening of the City of Mecca was the evidence of their real victory, “izaa jaa a nashrullahi wal fath”, when Allah’s help arrived and the city of Mecca had been opened (Surah an-Nasr: 1). This paper describes the hijrah as an historic event taking place in the context of rejection, persecution, and death threats carried out by the Quraysh infidels in Mecca against Muhammad and his followers. They moved to Yathrib or Medina to find new hope, glory and social transformation. Furthermore, this article offers some thoughts regarding the implementation of the idea of ????hijrah in the context of our common struggle to mitigate the prolonged covid-19 pandemic